BREAKING THE SILENCE: VOCABULARY AS THE KEY TO CONFIDENCE IN MUET SPEAKING - Nasir, Noormaizatul Akmar Muhamad; Yaacob, Nurul Husna; Razaki, Marina Muhammad; Arifin, Raihan Mohd; Ramanan, Banu (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This article revisits the critical role of vocabulary proficiency in shaping students’ confidence and anxiety during the Malaysian University English Test (MUET) speaking component. Drawing on data from a quantitative study involving 320 pre-university students across six institutions, it focuses on how lexical limitations influence both linguistic performance and psychological readiness. Using a structured Likert-scale questionnaire covering six constructs—vocabulary, grammar, pronunciation, confidence, motivation, and anxiety—the study identified vocabulary (M = 2.87, SD = 0.43) as the most significant area of difficulty, followed by grammar (M = 2.90, SD = 0.40). Confidence (M = 2.68, SD = 0.39) and anxiety (M = 2.74, SD = 0.41) showed strong associations with vocabulary proficiency, with Pearson correlation results indicating a negative correlation with confidence (r = –.61, p < .01) and a positive correlation with anxiety (r = .59, p < .01). These findings suggest that limited vocabulary not only hinders fluency and expression but also heightens anxiety and reduces self-assurance in oral performance. Anchored in Nation’s model of vocabulary acquisition, Bandura’s self-efficacy theory, and Krashen’s affective filter hypothesis, this study highlights vocabulary as both a linguistic foundation and an affective stabilizer, emphasizing the need for vocabulary-focused pedagogical interventions to enhance fluency, coherence, and confidence among MUET.